LARGE SHAREHOLDERS AND FIRM PERFORMANCE: EVIDENCE FROM TURKEY - Isik, Ozcan; Soykan, M. Erkan (European Scientific Journal, ESJ, 2013)
Using data for the period 2003-2010 of 164 industrial firms listed on Istanbul Stock Exchange (BIST-Borsa Istanbul), we empirically explore the impact of large shareholders on firm performance measured by ROA and Tobin’s Q. Empirical findings based on panel data analysis suggest that large shareholders have a significantly positive effect on the performance of the firms. In other words, the concentration of corporate ownership overcomes conflict of interest between the small shareholders and the managers. At the same time, in the case when share ownership of the large shareholder exceeds a certain level, once again, we find significant positive relation between large shareholders and firm performance. As a result, while we do not reject the validity of the efficient monitoring hypothesis, but rather the expropriating hypothesis in Turkey